Two-stage Anaerobic Reactor Design of SS 316 Material with Application of Penetrant Test Method (NDT) - Gea, Markus; Khaerudini, Deni Shidqi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
Abstract-- Anaerobic reactors are essential in processing organic waste, biomass, and wastewater into desired end products through a dark fermentation process. This process involves bacteria decomposing organic matter without light or oxygen, producing hydrogen gas, and other by-products. In this study, the design, manufacture, and testing of a two-stage anaerobic reactor of stainless steel 316 material were carried out carefully, considering dimensions, and material specifications. The device design process involved design simulation using SolidWorks, while the manufacturing stage involved material preparation, component forming, welding, and device installation. Testing was conducted using Nondestructive testing (NDT) methods to detect surface defects, and ensure the structural integrity of the reactor. This study provides an in-depth overview of the manufacturing process of a two-stage anaerobic reactor, including material preparation, welding, and NDT testing, hoping to contribute to developing more effective, and sustainable organic waste treatment technologies.